The effect of butterfly pea flower (Clitoria ternatea L.) tea consumption on blood pressure among patients with hypertension - Maryati Maryati; Naziyah Naziyah; Rian Agus Setiawan; Annisa Rahimatul Putri (Poltekkes Kemenkes Bandung, 2026)
Background: Hypertension remains a major public health problem worldwide and is associated with an increased risk of cardiovascular morbidity and mortality. In addition to pharmacological therapy, herbal-based non-pharmacological interventions are increasingly used as complementary therapies. Clitoria ternatea (butterfly pea) is a medicinal plant rich in anthocyanins and flavonoids, which are known to possess antioxidant and vasodilatory properties that may contribute to blood pressure reduction. Objective: To analyze the effect of butterfly pea tea consumption on blood pressure in patients with grade 1 hypertension. Methods: This study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 36 respondents were selected using purposive sampling in Tangerang City. The intervention consisted of butterfly pea tea prepared from 2 g of dried butterfly pea flowers brewed in 200 mL of hot water (approximately 90°C) for 10 minutes. The tea was consumed once daily in the morning after breakfast for seven consecutive days. Blood pressure was measured before and after the intervention using a calibrated digital sphygmomanometer. Results: There was a significant reduction in blood pressure following the intervention. The mean systolic blood pressure decreased from 149 ± 5.008 mmHg to 137 ± 4.060 mmHg, while the mean diastolic blood pressure decreased from 93 ± 3.140 mmHg to 80 ± 4.475 mmHg (p = 0.001). Conclusion: Butterfly pea tea consumption significantly reduced systolic and diastolic blood pressure in patients with grade 1 hypertension. This intervention has the potential to serve as a safe, affordable, and easily applicable complementary therapy in the community.